Effects of the COVID-19 pandemic on colorectal cancer surgery: Pandemic and colorectal cancer surgery - Hasırcı, İsmail and Ulutaş, Mehmet Eşref and Özden, Sabri and Arslan, Kemal (Journal of Surgery and Medicine, 2023)
Background/Aim: In accordance with the guidelines published during the COVID-19 pandemic, cancer operations, except for emergencies, were postponed. However, the effect of postponed surgical treatment on the outcomes of cancer cases has not yet been determined. Therefore, this study aimed to compare the clinical data and outcomes of patients who underwent surgery for colorectal cancer before and during the pandemic. Methods: This retrospective cohort study was conducted in the Department of General Surgery. Patients who underwent surgery for colorectal cancer during the pre-pandemic period (February 1, 2019-December 31, 2019) and pandemic period (August 1, 2020-June 30, 2021) were included. The patients’ demographic data, clinical and laboratory findings, clinical presentation, operation type, complications, and pathology results were retrospectively obtained by screening the patient files. Results: The study included a total of 183 patients, 91 in the pre-pandemic period and 92 in the pandemic period. During the pandemic period, the length of hospital stay was significantly shorter, but the rate of readmission after discharge was significantly higher (P<0.001, P=0.04). There was no significant difference between the two periods in terms of disease stage. During the pandemic period, the number of cases that underwent emergency surgery was significantly higher. The rates of mortality and postoperative complication rates were also significantly higher (P=0.04, P<0.001). Conclusion: The pandemic had serious effects on colorectal cancer cases. There was an increase in mortality and morbidity due to the increase in complicated cases.